Neo-Classicism in Modern Arabic Poetry - Al-Nadwi, Meraj Ahmad Meraj (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
Modern neo-classical poetry constitutes a phase of literature that can be sharply separated from its immediate ancestry. Arab poets composed by imitative versifiers who very rarely employed it as a means of expressing fresh human experience. The bulk of late medieval Diwans (collections of verse) are replete with rhetorical devices and puns. Rather than addressing the major issues of life and society. Neo-classicism is the outcome of the revival of ancient learning through technological advancement. The purpose of the present study is to discuss the new school of thought named Neo- Classicism in modern Arabic Poetry. It also highlights its role of neo classicism to development of Modern Arabic poetry.Â ÙŠØ´ÙƒÙ„ Ø§Ù„Ø´Ø¹Ø± Ø§Ù„ÙƒÙ„Ø§Ø³ÙŠÙƒÙŠ Ø§Ù„ØØ¯ÙŠØ« Ù…Ø±ØÙ„Ø© Ù…Ù† ØªØ·ÙˆØ± Ø§Ù„Ø£Ø¯Ø¨ ÙŠÙ…ÙƒÙ† ÙØµÙ„Ù‡ Ø¨Ø´ÙƒÙ„ ØØ§Ø¯ Ø¹Ù† Ø£ØµÙ„Ù‡ Ø§Ù„Ù…Ø¨Ø§Ø´Ø±. Ù…Ù† Ø§Ù„Ù†Ø¯Ø±Ø© Ù†Ø¬Ø¯ Ø§Ù„Ø´Ø¹Ø±Ø§Ø¡ Ø§Ù„Ø¹Ø±Ø¨ ÙŠØ³ØªØ®Ø¯Ù…ÙˆÙ†Ù‡ ÙƒÙˆØ³ÙŠÙ„Ø© Ù„Ù„ØªØ¹Ø¨ÙŠØ± Ø¹Ù† ØªØ¬Ø±Ø¨Ø© Ø¥Ù†Ø³Ø§Ù†ÙŠØ© Ø¬Ø¯ÙŠØ¯Ø©. Ø§Ù„Ø¬Ø²Ø¡ Ø§Ù„Ø£ÙƒØ¨Ø± Ù…Ù† Ø§Ù„Ø¯ÙˆØ§ÙˆÙŠÙ† ÙÙŠ Ø£ÙˆØ§Ø®Ø± Ø§Ù„Ø¹ØµÙˆØ± Ø§Ù„ÙˆØ³Ø·Ù‰ (Ù…Ø¬Ù…ÙˆØ¹Ø§Øª Ù…Ù† Ø§Ù„Ø´Ø¹Ø±) Ù…Ù„ÙŠØ¦Ø© Ø¨Ø§Ù„Ø£Ø¯ÙˆØ§Øª Ø§Ù„Ø¨Ù„Ø§ØºÙŠØ© ÙˆØ§Ù„ØªÙˆØ±ÙŠØ©. Ø¨Ø¯Ù„Ø§ Ù…Ù† Ù…Ø¹Ø§Ù„Ø¬Ø© Ø§Ù„Ù‚Ø¶Ø§ÙŠØ§ Ø§Ù„Ø±Ø¦ÙŠØ³ÙŠØ© Ù„Ù„ØÙŠØ§Ø© ÙˆØ§Ù„Ù…Ø¬ØªÙ…Ø¹. Ø§Ù„ÙƒÙ„Ø§Ø³ÙŠÙƒÙŠØ© Ø§Ù„Ø¬Ø¯ÙŠØ¯Ø© Ù‡ÙŠ Ù†ØªÙŠØ¬Ø© Ø¥ØÙŠØ§Ø¡ Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù‚Ø¯ÙŠÙ… Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„ØªÙ‚Ø¯Ù… Ø§Ù„ØªÙƒÙ†ÙˆÙ„ÙˆØ¬ÙŠ.Â  Ø§Ù„ØºØ±Ø¶ Ù…Ù† Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù‡Ùˆ Ù…Ù†Ø§Ù‚Ø´Ø© Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„ÙÙƒØ±ÙŠØ© Ø§Ù„Ø¬Ø¯ÙŠØ¯Ø© Ø§Ù„Ù…Ø³Ù…Ø§Ø© Ø§Ù„ÙƒÙ„Ø§Ø³ÙŠÙƒÙŠØ© Ø§Ù„Ø¬Ø¯ÙŠØ¯Ø© ÙÙŠ Ø§Ù„Ø´Ø¹Ø± Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ø§Ù„ØØ¯ÙŠØ«. ÙƒÙ…Ø§ ÙŠØ³Ù„Ø· Ø§Ù„Ø¶ÙˆØ¡ Ø¹Ù„Ù‰ Ø¯ÙˆØ±Ù‡Ø§ Ø§Ù„ÙƒÙ„Ø§Ø³ÙŠÙƒÙŠ Ø§Ù„Ø¬Ø¯ÙŠØ¯ ÙÙŠ ØªØ·ÙˆÙŠØ± Ø§Ù„Ø´Ø¹Ø± Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ø§Ù„ØØ¯ÙŠØ«.Â